The Benefits and Challenges of the Gig Economy: Perspective of Gig Workers and Small Medium and Micro Enterprises (SMMEs) in South Africa - Sudhika Palhad; Stanley Onwubu; Rasmi Singh; Rookmoney Thakur; Surendra Thakur; Gugu Mkhize (African Journal of Inter-Multidisciplinary Studies, 2023)
Digital work, otherwise referred to as 'gig' work, is heralded as a useful strategy that could help bridge the unemployment rate in South Africa by connecting job seekers and business organisations across the global spectrum. The purpose of this paper was to explore the benefits and challenges of the gig economy on SMMEs in South Africa. In this study, an interpretive research paradigm was followed to explore the benefits and challenges of the gig economy in the SMMEs in South Africa. Semi-structured focus group interviews were conducted with 20 participants, consisting of thirteen gig workers (n=13) and seven business organization employees (n=7). The data collected were thematically analysed with the aid of NVivo v12 software (QSR International Pty Ltd, 2015). The participants held the view that the gig economy can promote business growth and economic inclusion, and help organisations better manage their resources. While gig work offers some advantages, the participants highlighted concerns surrounding the lack of clear policy, occupational vulnerability, precarity, platform-based work, and the risks of gig work. The study suggests that gig work is critical to advancing the growth of Small, Medium, and Micro Enterprises (SMMEs) in South Africa.